The effect of social support on job performance through organizational commitment and innovative work behavior: does innovative climate matter? - Vuong, Bui Nhat; Tushar, Hasanuzzaman; Hossain, Syed Far Abid (Asia-Pacific journal of business administration, 2023)
PurposeThe purpose of this study is to explore the influence of social support (SS) on job performance (JP) through the mediating role of organizational commitment (OC) and innovative work behavior (IWB) as well as the moderating role of innovative climate (IC).Design/methodology/approachThe present research used a self-report questionnaire from a sample of 694 full-time employees in the Vietnamese small and medium-sized enterprises (SMEs) and the partial least squares structural equation modeling (PLS-SEM) to test studied hypotheses.FindingsThe findings revealed that a high level of social support at work could enhance employees’ job performance. The findings also indicated that this positive relationship was partially mediated by organizational commitment and innovative work behavior. Besides, an innovative climate strengthened the positive association between social support and innovative work behavior.Practical implicationsThe result of this study provides practical implications for the contemporary human resource (HR) management practice and policy in organizations. Organizations may have an enduring HR policy to strengthen robust social support to enhance employees’ job performance at work.Originality/valuePerhaps, the largest benefit of this research is that the research provided statistical evidence of the relational values between a system of variables to add to the limited academic literature available on the subject. While plenty of literature suggested that social support played a crucial role in organizational commitment, innovative work behavior, and job performance, the researchers failed to determine if a moderating role of innovative climate existed between social support and innovative work behavior. This study filled the gap in literature by introducing that a moderation exists of IC between SS and IWB instead of using SS and IWB as separate factors.